используем формулу логарифма частного
![log_a b-log_a c=log_a {\frac{b}{c}} log_a b-log_a c=log_a {\frac{b}{c}}](https://tex.z-dn.net/?f=log_a+b-log_a+c%3Dlog_a+%7B%5Cfrac%7Bb%7D%7Bc%7D%7D)
;
![image](https://tex.z-dn.net/?f=a%3E0%3Bb%3E0%3Bc%3E0%3Ba+%5Cneq+1)
0;b>0;c>0;a \neq 1" alt="a>0;b>0;c>0;a \neq 1" align="absmiddle" class="latex-formula">
=
используем формулу логарифма степеня и логарифма за одинаковым основанием
![image](https://tex.z-dn.net/?f=log_a+b%5Ec%3Dc%2Alog_a+b%3Ba%3E0%3Ba+%5Cneq+1%3B+b%3E0%3B)
0;a \neq 1; b>0;" alt="log_a b^c=c*log_a b;a>0;a \neq 1; b>0;" align="absmiddle" class="latex-formula">
![image](https://tex.z-dn.net/?f=log_a+a%3D1%3B+a%3E0%3Ba+%5Cneq+1)
0;a \neq 1" alt="log_a a=1; a>0;a \neq 1" align="absmiddle" class="latex-formula">
=
ответ: 4